2002
DOI: 10.1007/s00442-002-0952-2
|View full text |Cite
|
Sign up to set email alerts
|

How much variance can be explained by ecologists and evolutionary biologists?

Abstract: The average amount of variance explained by the main factor of interest in ecological and evolutionary studies is an important quantity because it allows evaluation of the general strength of research findings. It also has important implications for the planning of studies. Theoretically we should be able to explain 100% of the variance in data, but randomness and noise may reduce this amount considerably in biological studies. We performed a meta-analysis using data from 43 published meta-analyses in ecology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

37
272
9
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(320 citation statements)
references
References 46 publications
37
272
9
2
Order By: Relevance
“…There also was a significant interaction between host condition and social environment (F 2,174 ϭ 4.82, P ϭ 0.009), with the overall full model explaining 46.7% of the variation in the data. This result is relatively strong, explaining Ϸ13 times the average amount of variation (3.6%) explained in evolutionary studies (31).…”
Section: Resultsmentioning
confidence: 85%
“…There also was a significant interaction between host condition and social environment (F 2,174 ϭ 4.82, P ϭ 0.009), with the overall full model explaining 46.7% of the variation in the data. This result is relatively strong, explaining Ϸ13 times the average amount of variation (3.6%) explained in evolutionary studies (31).…”
Section: Resultsmentioning
confidence: 85%
“…Our global GLM that contained all recorded predictors of human-to-human transmission in all viruses as fixed effects had R 2 = 0.446, a value that is relatively high for an evolutionary or ecological study (30). A model incorporating duration of infection, outer envelope status, segmentation (i.e., segmented or nonsegmented), mode of transmission, and mortality rate had the lowest AICc (Table 1).…”
Section: Resultsmentioning
confidence: 98%
“…Compared with the PC of body masculinity used in the previous analyses, this assessment of landmark joint configuration is less dependent on hip and breast fat distribution. Because female bodily attractiveness is largely associated with fat distribution (8,11,30), we expected that joint configuration would be a better indicator of attractiveness and phenotypic quality in males than in females. The locations (x-y-z coordinates) of 18 landmarks were estimated using NX12 scanning software and the [TC] 2 body scanner.…”
Section: Resultsmentioning
confidence: 99%
“…However, a study that tested directly for publication bias (29) did not find a significant difference in effect sizes (adjusted for sample size) between published and unpublished studies. Another report shows that the effect sizes in the study of FA are within the range of other fields in ecology and evolutionary biology (30). Considering the strong theoretical rationale for expecting bodily characteristics to function as reliable signals of quality, it is notable that no published study has demonstrated significant relationships between human body attractiveness, or shape-based secondary sex characteristics, and FA.…”
mentioning
confidence: 94%